Receiving Stocker Cattle Performance is Similar With Either Corn or Sorghum Wet Distillers Grains - A. C. Vesco; A. K. Sexten; E. Titgemeyer; W. R. Hollenbeck; L C. Grimes; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Distillers grains are an excellent energy and protein feed source for beef cattle. Corn distillers grains have been fed to beef cattle for many years, but sorghum distillers grains are becoming more popular and may be more cost effective than corn. Sorghum is very comparable to corn in terms of energy, but has a higher crude protein value. All distillers grains are available in a wet and dry form. The moist texture of wet distillers grains can help to reduce sorting at the bunk and appears to improve intake in young calves. The objective of this study was to evaluate the effect of corn and sorghum wet distillers grains on performance and digestibility of receiving stocker calves.
Keywords: corn wet distillers grains; sorghum wet distillers grain; receiving stocker cattle